Co-morbid conditions in use of recombinant tissue plasminogen activator (rt-PA) for the treatment of acute ischaemic stroke. (23rd August 2016) - Nathaniel, Thomas I.; Cochran, Thomas; Chaves, Jose; Fulmer, Eric; Sosa, Crystal; Yi, Sara; Fredwall, Megan; Sternberg, Shannon; Blackhurst, Dawn; Nelson, Alfred; Leacock, Rodney
Abstract: Background : The objective of this study was to characterize the comorbidities in a population of patients with an acute ischaemic stroke, comparing patients that received recombinant tissue plasminogen activator (rt-PA) to those that did not receive rt-PA. Method : In a retrospective sample of 663 patients admitted for acute ischaemic stroke, this study analysed the effects of co-morbid conditions in the use of rt-PA. It determined non-cerebrovascular risk factors (comorbidities) that differentiate patients who received rt-PA from those who did not receive rt-PA. Result : Patients with a history of carotid stenosis, CHF and previous strokes are significantly ( p < 0.05) associated with high risk of not receiving rt-PA. A significant number of patients with a history of hypertension and smoking received rt-PA ( p < 0.05). Conclusion : The findings indicate that certain risk factors including carotid stenosis, CHF and previous stroke history impact the treatment of patients with acute ischaemic stroke, specifically the decision to administer rt-PA. Treatment with rt-PA is dependent on stroke severity and onset to treatment time, but the findings suggest that rt-PA use may also depend on patient comorbidities.